2000
DOI: 10.1161/01.str.31.5.1144
|View full text |Cite
|
Sign up to set email alerts
|

Early Exclusive Use of the Affected Forelimb After Moderate Transient Focal Ischemia in Rats

Abstract: Background and Purpose-Previous work by researchers in our laboratory has shown that in the rat, the exclusive use of the affected forelimb during an early critical period exaggerates lesion volume and retards functional recovery after electrolytic lesions of the forelimb sensorimotor cortex. In the present study, we examined the effects of exclusive use of the affected forelimb after middle cerebral artery occlusion (MCAO). Methods-Ischemia of moderate severity was produced in male Long-Evans rats through 45 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
104
4
4

Year Published

2001
2001
2016
2016

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 172 publications
(115 citation statements)
references
References 48 publications
3
104
4
4
Order By: Relevance
“…15,[62][63][64][65][66] Considerable progress is being made in designing useful, evidence-based outcome measures for human stroke diagnosis and research. It is not easy to match deficits in rats and people, but test selection and interpretation of the nature of the deficit is critical in both if translational research is to be successful.…”
Section: Resultsmentioning
confidence: 99%
“…15,[62][63][64][65][66] Considerable progress is being made in designing useful, evidence-based outcome measures for human stroke diagnosis and research. It is not easy to match deficits in rats and people, but test selection and interpretation of the nature of the deficit is critical in both if translational research is to be successful.…”
Section: Resultsmentioning
confidence: 99%
“…The latter result raises the possibility of a limit on the amount of RA training that is beneficial. Expansion of neural injury and reduced restoration of function associated with early forced use of a forelimb after unilateral brain injury has been seen in rats [37][38][39][40]. Although the applicability of these results to human trials has not been demonstrated, they point out the need to consider intensity, total dose, and timing of training in trials of novel therapeutic methods and devices.…”
Section: Discussionmentioning
confidence: 97%
“…1). These tests included ipsi-and contralateral assessment of fore-and hindlimb use to assess motor function, locomotion, limb use, and limb preference, 47,48 toe spread to assess gross motor response, 49 placing to assess visual and vestibular function, 50,51 catalepsy rod test to assess postural support and mobility, 52 bracing to assess postural stability and catalepsy, 53,54 and air righting to assess dynamic vestibular function. 55,56 Scoring ranged from 0 (severely impaired) to 5 (normal strength and function).…”
Section: Ibudilast (Mn166) Administrationmentioning
confidence: 99%